2005
DOI: 10.1590/s0103-97332005000400014
|View full text |Cite
|
Sign up to set email alerts
|

A Mössbauer effect study of the Soledade meteorite

Abstract: We performed a Mössbauer spectroscopy study of the iron meteorite Soledade. This meteorite, which consists of a metallic matrix, is an octahedrite with polycrystalline troilite, cohenite, schreibersite and rhabdites as major constituents. A chemical analysis indicates 6.78 % Ni, 0.46% Co, besides traces of Cu, Cr, Ga, Ge, As, Sb, W, Re, Ir and Au. No traces of silicates have been found and no oxygen was detected. Iron is appearing in the austhenitic phase and alloyed with nickel. An analysis of the Mössbauer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This finding is consistent with the presence of Ni in the α-Fe structure, as suggested by the in situ MER APXS analysis of the meteorite target and with the conclusion put forward by Morris et al (2006). It is also consistent with data for the ironnickel meteorite Soledade, which has a Ni concentration of 6.8 wt%, and for which a hyperfine field of 34.4 T at room temperature (Paduani et al 2005) was measured. This value is higher by about 1.4 T compared to the hyperfine field that is typical for α-Fe at room temperature, i.e., 33.0 T.…”
Section: Introductionsupporting
confidence: 90%
“…This finding is consistent with the presence of Ni in the α-Fe structure, as suggested by the in situ MER APXS analysis of the meteorite target and with the conclusion put forward by Morris et al (2006). It is also consistent with data for the ironnickel meteorite Soledade, which has a Ni concentration of 6.8 wt%, and for which a hyperfine field of 34.4 T at room temperature (Paduani et al 2005) was measured. This value is higher by about 1.4 T compared to the hyperfine field that is typical for α-Fe at room temperature, i.e., 33.0 T.…”
Section: Introductionsupporting
confidence: 90%
“…Therefore, it is not possible to reproduce extraterrestrial Fe-Ni-Co alloys in the terrestrial conditions while some features of meteorite metallic iron may be useful for new alloys development. Mössbauer spectroscopy is a useful tool for study iron meteorites (see, for instance, [2][3][4][5]). Therefore, we have applied Mössbauer spectroscopy to study some iron meteorites in order to evaluate the relationship of the hyperfine parameters and metal phases in meteorites with variations in Ni concentration [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A discussion ab questionable term "antitaenite" was already reported in Part I, Section 6.1 [1]. Mo the authors of [64], who also observed the paramagnetic singlet in the Mössbaue trum of Santa Catharina, determined the Ni content of 28 at.% for this compone corresponded to the well-known paramagnetic γ-Fe(Ni) phase (paramagnetic taen A comparison of the different areas of the coarse octahedrite Soledade IAB-Mössbauer spectroscopy was carried out in [71]. The Fe-Ni alloy contained about 6 Ni, indicating the α-Fe(Ni, Co) phase.…”
Section: Iron Meteoritesmentioning
confidence: 99%
“…In co the surface spectrum mainly showed the presence of ferric compounds in the m and paramagnetic states. A comparison of the different areas of the coarse octahedrite Soledade IAB-MG by Mössbauer spectroscopy was carried out in [71]. The Fe-Ni alloy contained about 6.7 at.% Ni, indicating the α-Fe(Ni, Co) phase.…”
Section: Iron Meteoritesmentioning
confidence: 99%